Trust in nutrition, subjective norms and urban consumers’ purchase behavior of quinoa products: explanation based on preference heterogeneity - Wang, Chan; Fu, Xiaoyan; Li, Caixia; Liu, Zengjin; Wang, Shanshan; Chen, Tinggui; Jia, Lei (Frontiers in Nutrition, 2024)
With the increase of disposable income and the awakening of health consciousness of Chinese residents, higher requirements have been put forward for the nutritional value of food. To meet the market demand and promote the high-quality development of the whole quinoa industry chain, this study aimed to analyze the purchase behavior of quinoa from the aspects of nutritional trust and subjective norms. Based on 1078 micro-survey data from 16 administrative districts in Shanghai, this paper empirically examined the influence of trust in nutrition and subjective norms on consumers' purchase behavior and willingness to pay of quinoa products, and further investigated the moderating effect of preference heterogeneity. Results show that 38.22% of respondents have purchased quinoa products. Trust in nutrition and subjective norms can not only promote their purchasing behavior, but also improve consumers' willingness to pay for quinoa products.The analysis of the moderating effect shows that both the purchase behavior and the willingness to pay are affected by the preference heterogeneity, and the cognitive preference will weaken the positive influence of subjective norms on the purchase behavior, while the nutritional preference of consumers can strengthen the positive influence of trust in nutrition on the willingness to pay. Therefore, this paper suggests that strengthens research and development of products market oriented, implements certification and labeling schemes for nutrition and other properties of products, intensifies publicity and promotion of products to enhancing consumers' awareness of healthy diet.